Penguatan kemampuan bercerita anak melalui pendampingan guru dan orang tua berbasis media audio Spotify - Yuniarti; Iin Maulina; Raizka Triana (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2026)
Storytelling is an aspect of early childhood language development because it provides children with opportunities to listen, understand, and express ideas. However, storytelling activities at TK Aisyiyah Bustanul Athfal Teluk Kapuas tend to rely on conventional methods, with limited use of digital media, while parental involvement in supporting children’s literacy activities at home remains low. This program aimed to support children’s storytelling skills through audio media and strengthen collaboration between teachers and parents in the process. The program was conducted at TK Aisyiyah Bustanul Athfal Teluk Kapuas, Kubu Raya Regency, involving teachers and parents as partners. A participatory and collaborative approach was applied through stages, including socialization, needs identification, training in the use of Spotify as an audio medium, storytelling assistance, and evaluation through observation, interviews, and satisfaction questionnaires. The results showed that teachers and parents gained understanding and skills in selecting and using audio content for storytelling activities. Audio-based stories encouraged children to participate in listening to and retelling stories using their own words. Collaboration between teachers and parents began to develop through storytelling activities conducted at school and continued at home. The program produced an electronic pocketbook containing guidelines for using Spotify-based audio media and recommendations for story content suitable for early childhood. These findings indicate that Spotify-based audio media can serve as an alternative medium for storytelling activities while supporting teacher and parental involvement in children’s literacy development. The program provides a practical model for integrating audio into storytelling activities across school and home learning environments.